Modelos não lineares mistos em estudos de crescimento de frango de corte - Yamanaka, Sandra Emiko (Universidade Federal de São Carlos, 2018)
Premix is the main source of micronutrients such as vitamins, probiotics, prebiotics, enzymes, and macro and microminerals in poultry feed, that are included in the ration to improv the digestion of food and the performance of the selected lineage. Therefore, the knowledge of these compounds has great importance in studies on the growth of broilers. Nonlinear models are widely used in these studies, seeking to estimate parameters related to adult weight and growth rate through of methods that consider correlation between the repeated measures in the same chicken and the heterogeneity of the variances of the responses. As individual differences can occur for the weight response of birds, the use of mixed nonlinear models is proposed, allowing the nonlinear function on fixed and random effects, which may solve the problem of explaining variation among these kind of birds. In this work two common alternatives of growth data analysis were used and their results were compared with the approach using the mixed nonlinear model. The non-linear Gompertz model was used to explain the relationship between body weight and age, in broilers fed with feed supplemented with three different brands of premixes available in the market. The measurements of the weighings were collected in seven rounds at baseline and at 1st, 2nd, 3rd, 4th, 5th and 6th weeks. There data were obtained from a completely randomized design experiment with three hundred and seventy chickens from the Cobb line, three treatments and seven replicates.
Nonlinear mixed models in growth studies of broiler
Keywords: Modelo não Linear Misto; Medidas Repetidas; Variabilidade; Premixes; Mixed nonlinear model; Repeated measures; Variability; Premixes; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA